The Influence of External Radiation on the Emission Properties of H- and He-like Argon Ions in High Temperature Plasma - Roman K. Kulikov; Igor Yu. Skobelev; Evgeny D. Filippov (Atoms, 2025)
In the present work, the influence of external X-ray radiation on the kinetics of multicharged ions in high-temperature plasma is investigated. A generalized diagnostic approach is proposed for the electron density and temperature measurements of photo-pumped plasma based on the relative intensity of the H-like ion resonance line and its dielectronic satellites. Based on detailed kinetic calculations performed for argon plasma, the conditions under which these techniques can be applied without modification to the photo-pumped plasma are determined, and the relative intensities of these lines are calculated for cases where the external influence significantly alters the kinetics of their excitation. The development of such diagnostic methods is of particular importance for the experiments with powerful X-ray free-electron lasers and thermonuclear laser plasma.